Transatlantic defence procurement : EU and US Defence Procurement Regulation in the Transatlantic defence market / Luke R.A. Butler. - Butler, Luke R. A. (Cambridge University Press, 2017)
This volume constitutes the first ever attempt to establish a basis for comparative research on defence procurement regulation. For decades there has been repeated emphasis on the extent to which barriers to trade in Europe and the US prevent a more competitive defence market. Transatlantic Defence Procurement offers a first analysis of the potential impact of defence procurement regulation itself as a barrier to trade between the US and EU. Part I examines the external dimension of a new EU Defence Procurement Directive, focusing on its implications for third countries, in particular the US. Part II examines foreign access and treatment under US law. Part III maps a future research agenda that is essential for a more systematic understanding of legal barriers to transatlantic defence trade. The book provides context for future initiatives, ranging from reformed market access arrangements to a Defence Transatlantic Trade and Investment Partnership and beyond.